MANAJEMEN PTKIS DI TENGAH PANDEMI COVID-19 - Rahman, Kholilur (Tarbiyatuna : Kajian Pendidikan Islam, 2020)
Pandemic Covid-19 is a challenge for campus leaders. Covid-19 in Indonesia brought significant impact on the implementation of tridharma PTKIS. Minister of Education and Culture, Nadiem Anwar Makarim finally required all educational institutions to apply online learning. Education is the mandate of the Constitution. The Government should be grateful to PTKIS who continue to serve the student education rights. In the present condition, PTKIS should be invited together to find the best solution. This is done so that the service and quality of learning can still be maintained. The fate of lecturers and private employees remains assured.